Spray mixture deposition on different vegetative volumes of Coffea arabica l. - Santinato, Felipe; Alves Ruas, Renato Adriane; Silva, Carlos Diego; da Silva, Rouverson Pereira; Reis Gonçalves, Victor Afonso; de Sousa Júnior, José Márcio (Coffee Science - ISSN 1984-3909, 2017)
The arrangement of branches and leaves overlap in coffee plants hinder the penetration of sprayed mixture. Therefore, to determine the volume of appropriate syrup, it is important to check the condition of the crop leafiness before application. The objective of this study was to evaluate the deposition of spraying of pesticides in coffee plantations applied on different vegetative volumes. The treatments were arranged following split plot in each growing volume (5,000; 7,500; 10,000 and 17,500 m3 ha-1). And five volumes of syrup portions (150, 300, 450, 600 and 750 L ha-1) and the subplots three positions in the coffee canopy (upper, middle and lower) with four replicates. In the four volumes vegetative studied no significant interaction (p > 0.05) between the applied volume and the different vegetative volumes. However, the vegetative volume of 5000.0 and 17500.0 m3 h-1 depositions was increased with increasing flow, which can be assigned the foliar density. There was no statistical difference (p> 0.05) between the means of deposition in different thirds (heights) in the coffee plants canopy in vegetative volumes 5000.0 m3 ha-1, 10000.0 m3 ha-1 and 17500.0 m3 h-1. However, the volume of 7500.0 m3 ha-1 showed higher deposition in the middle third from the bottom third. The deposition is higher as it increases the volume of applied syrup. In plants with reduced leaf density, there is an increase in the deposition. The deposition is largest in the middle third relative to the lower third.